Biomass and sugar content of some varieties of sorghum (Sorghum Bicolor L. Moench) on dry land forest as feedstock bioethanol - Gamawati Adinurani, Praptiningsih; Rahayu, Sri; Sulistiyo Budi, Luluk; Nindita, Anggi; Soni, Peeyush; Mel, Maizirwan (EDP Sciences, 2018)
The possibility of sustainable use of sorghum as raw material for bioethanol needs to be supported by evaluation and selection of sorghum varieties for high biomass production and sugar content. An experiment was conducted on forest dry land , altitude 63 m asl. This research aimed to determine the interaction of sorghum varieties and mycorrhiza on biomass production and the high sugar content. The experiment was a two factor (varieties and dosage of mycorrhiza plus) in a randomized complete block design with three replications. The varieties were Suri 3, Kawali, Super 2, Suri 4. Dosage of mycorrhiza plus (5, 10, 15) g per plant. The interaction only significant on a number of internodes and bagasse. There are no effects of dosages mycorrhiza plus, however, varieties of sorghum have significant effects on many variables measured. The highest amount of biomass include the stem height (301.28 cm), stem Dry Weight (DW) is 23.48 t ha–1 , leaf DW (4.65 t ha–1 ), panicle DW (11.35 t ha–1 ) and biomass DW (39.98 t ha–1 ) were obtained in varieties Super 2. Sugar content (16.93 %) was obtained in varieties Suri 3 and juice production (2 742.86 L ha‒1 ) in varieties Suri 4.